PEMBENTUKAN KOMUNITAS KPOP DI KOTA PEKANBARU - Vanny Wildani; Swis Tantoro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
The process of globalization brought the Korean Wave virus into Pekanbaru and caused the emergence of many Korean culture lovers, especially among young people. Indonesian television broadcasts a lot of Korean dramas that attract the attention of the Indonesian people, not only the drama, Korean Pop music is also the most interested in teenagers in Pekanbaru. Finally, Korean pop culture can form Kpop fanclubs in Indonesia to be widespread in cities such as Pekanbaru city. The method used in this research is qualitative where the researcher gets three subjects who are selected using purposive sampling by meeting the criteria determined by the researcher. Through this study, it was concluded that the factors for the formation of the Pekanbaru KPopers Community were due to the similarity of interests and interests with KPop culture, as a medium for sharing and exchanging information. Social interactions that occur in this community arise after the fulfillment of social interaction requirements, namely social contact, which is best done indirectly by using TV and internet media and then social communication which aims to convey messages and information related to KPop. Then the consumptive behavior carried out by Pekanbaru kpopers members is not only a fulfillment of desires or desires, but becomes a consumption. They realize the impact and benefits of being K-popers, from the positive things they become diligent in saving, independent and work hard to achieve something and from the negative they become wasteful in buying K-pop goods, spending money on Kpop activities such as ganthering, watching concerts and other activities. Other Kpop as well as their activities are often busy in their own world. Keywords: Social Group, Social Interaction, Korean pop.